Attrition and attrition-resistance of oxygen carrier in chemical looping process – A comprehensive review. (1st February 2023) - Liu, Fang; Song, Chen; Zhu, Dan; Li, Caifu; Ai, Lun; Xin, Chunmei; Zeng, Xingyang; Zeng, Liang; Huang, Neng; Yang, Li
Highlights: Evolution on oxygen carrier's property during long time operating is discussed. The attrition mechanism, sources and measurement methods are reviewed. Mathematical and simulation research of particles attrition are summarized. The methods for anti-attrition of oxygen carrier are proposed. Abstract: Chemical looping technology is an innovative method for CO2 capture. Oxygen carrier (OC) is the key to the chemical looping process. The mechanical properties of OC are a major uncertainty limiting the economics of the technology. The chemical looping process usually operates as a fluidized bed, during which OC is constantly subjected to mechanical, thermal and chemical stresses, leading to severe attrition. In addition, the long operating time also greatly accelerates the attrition process. This study provides a comprehensive review of OC attrition, including the parameter changes in long-term operation, mechanisms and measurement methods of attrition, models for simulation, methods to reduce attrition, and sensitivity analysis of attrition. Numerous studies have found severe OC attrition in operations. However, there is no systematic understanding of OC attrition in the chemical looping field. Therefore, in future studies, it is recommended to provide systematic and complete particle parameters to construct a more complete database. On this basis, further insight into the attrition mechanism of OC is expected to be obtained.